SOCIAL SATIRE IN COVID-19 MEDIA CARTOONS IN CÔTE D'IVOIRE: A MULTIMODAL CRITICAL DISCOURSE ANALYSIS (Journal of Contemporary Philology, 2024)
This paper adopts an interdisciplinary approach involving satire, multimodality, and critical discourse to investigate the interplay of semiotic modes used in Gbich! COVID-19 cartoons. It examines how these cartoons depict the socioeconomic and political realities of Ivorian citizens during the pandemic and how they served as tools to raise public awareness, critique governmental and global (in)actions, and challenge existing traditional structures and practices. The study is based on 6 purposively selected COVID-19 front-page cartoons of Gbich!, a prominent satirical and humorous newspaper in Côte d'Ivoire. The data were analysed using Kuiper's Perceptual Theory of Satire and Machin and Mayr's Multimodal Critical Discourse Analysis. The findings reveal that the newspaper satirised issues reflecting domestic, local, and global discourses during the pandemic. It highlighted power dynamics within family structures during crises, as well as between the virus, citizens and global entities. The paper concludes that the newspaper elicited discussions on gender roles and expectations, information management, crisis management and prioritisation of responses during emergencies. Moreover, it impressed its ideological stance on solidarity, power and marriage to its audience.
Keywords: semiotic modes; satire; COVID-19 cartoons; power dynamics; ideology; Ivorian citizens